The Maximum Degree of an Exponentially Distributed Random Graph - Harahap, Desti Alannora; Suwilo, Saib; Mardiningsih (Politeknik Ganesha Medan, 2022)
Let G G (n, p) be a graph on n vertices where each pair of vertices is joined independently with probability p for 0 < p < 1 and q = 1 p. In this work, we introduce weighted random graf G with exponential distribution and investigate that the probability that every vertex of G has degree at most np + b√pqn is equal to 0.595656764.